Artificial Intelligence Will Be Able To Change Lifestyles And Financial Literacy Towards The Era Of Society 5.0 - Riyani, Diah (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
This article makes predictions about the future of AI and its development, which is getting faster and faster, and whether AI can change a person's lifestyle and financial literacy in the future towards society 5.0. The evolution of mankind has been dominated by industrial revolutions, one after another, which have changed the face of the modern world. The fifth industrial revolution is dawning on the world in unexpected ways as we rely more and more on Industry 4.0 technologies, including artificial intelligence (AI), big data (BD), the Internet of Things (IoT), digital platforms, augmented and virtual reality, and 3D printing. AI can change style, and AI can also change financial literacy by using advanced AI technology. The approach used in this research is qualitative, while the type of research used is library research. In the past, in an information society, the common practice was to collect information via the network and have it analyzed by humans. In Society 5.0, however, people, things, and systems are all connected in cyberspace, and optimal results obtained by AI exceeding the capabilities of humans are fed back to physical space. This process brings new value to industry and society in ways not previously possible.